Berberine improves intralipid-induced insulin resistance in murine - Dong Zhen-hua; Lin Hai-yan; Chen Fu-lian; Che Xiao-qi; Bi Wen-kai; Shi Shu-long; Wang Jing; Gao Ling; He Zhao; Zhao Jia-jun (Acta Pharmacologica Sinica, 2021)
Insulin resistance (IR) is a major metabolic risk factor even before the onset of hyperglycemia. Recently, berberine (BBR) is found to improve hyperglycemia and IR. In this study, we investigated whether BBR could improve IR independent of hyperglycemia. Acute insulin-resistant state was induced in rats by systemic infusion of intralipid (6.6%). BBR was administered via different delivery routes before or after the beginning of a 2-h euglycemic-hyperinsulinemic clamp. At the end of experiment, rats were sacrificed, gastrocnemius muscle was collected for detecting mitochondrial swelling, phosphorylation of Akt and AMPK, as well as the mitochondrial permeability regulator cyclophilin D (CypD) protein expression. We showed that BBR administration markedly ameliorated intralipid-induced IR without affecting blood glucose, which was accompanied by alleviated mitochondrial swelling in skeletal muscle. We used human skeletal muscle cells (HSMCs), AML12 hepatocytes, human umbilical vein endothelial cells, and CypD knockout mice to investigate metabolic and molecular alternations. In either HSMCs or AML12 hepatocytes, BBR (5 μM) abolished palmitate acid (PA)-induced increase of CypD protein levels. In CypD-deficient mice, intralipid-induced IR was greatly attenuated and the beneficial effect of BBR was diminished. Furthermore, we demonstrated that the inhibitory effect of BBR on intralipid-induced IR was mainly mediated by skeletal muscle, but not by intestine, liver, or microvasculature; BBR administration suppressed intralipid-induced upregulation of CypD expression in skeletal muscle. These results suggest that BBR alleviates intralipid-induced IR, which is related to the inhibition of CypD protein expression in skeletal muscle.